Knowledge Regarding Infertility among the People of Reproductive Age Group - Sharma, Saraswati; Bhandari, Sushila Devi (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Fertility or the ability to produce children has a positive social value whereas; infertility has a negative social value in which it means inability couple to have children even though after living a normal sexual life and does not use any contraceptive devices for one year. Infertility can be primary or secondary and primary infertility means when a couple has never been able to conceive; secondary infertility means a couple who has previously conceived a pregnancy, but is unable to conceive again after a full year.The aim of the study was to assess the knowledge regarding infertility among the people of reproductive age group.Methods: Cross sectional was done to “Assess the knowledge regarding infertility among the people of reproductive age group "at Gynae OPD of Shree Birendra Hospital.  The Non-probability purposive sampling technique was used. The study population was 110 and study period was 2071/3/15-2071/4/25. Semi-structured questionnaire was used.  The data were analyzed by using SPSS 20.Results: No significant relationship was established (p=0.5) between the knowledge about infertility and age. There was approximately equal number of respondents who had knowledge of infertility in the variation of age group. The proportion of knowledge in male respondents (93.8%) is comparatively more than the female (84.6%). The proportion of knowledge of infertility according to the variation of ethnicity was similar to each other. Likewise the proportion of knowledge of infertility by occupation (p=0.216) and marital status (p=0.122) were also not significantly different.  Conclusion:  The knowledge of infertility was not associated to the age, occupation and marital status.